Experimental and numerical analysis to collapse of a framed structure subjected to seismic loading - Domizio, Martin Norberto (2015)
The nonlinear numerical analysis to collapse of civil structures presents several difficulties, even for mechanically well-characterized materials, such as steel. In the case of steel, where the nonlinear constitutive equation is one of the simplest and best known, in many cases there are large differences when the numerical analysis and experimental results are compared. In this paper, the results of an experimental and numerical analysis of a single degree of freedom (SDOF) steel structure are presented. The structure was subjected to near fault earthquakes that caused nonlinear behavior of their components and structural collapse. The experimental model was tested on a shaking table. Complementary tests were performed to characterize the properties of the steel employed, and thus define the parameters used in the numerical simulation. After the calibration of the nonlinear material model, a comparison is made between the experimental and numerical results obtained. Finally, a numerical study, following the modeling methodology obtained from the numerical-experimental analysis, is performed to quantify the influence of the P-Delta effect on the structural collapse.